Impact of Ransomware on Cybersecurity (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
This paper attempts to discover ransomware exposing the lack of cyber-security. It intends to elicit attention with regards to ransomware, a newly emerged cyber threat and to help organizations; IT practitioners understand the need for cyber security knowledge and awareness plus types of tools used. The paper also discusses methodologies trends and research recommendation on cyber-security threats and provides probative strategic strategy.